Molecular detection of pathogenic Leptospira spp. in urban rodents from wet markets in northeast Malaysia - Kamaruzaman, Intan Noor Aina; Mokhtar, Muhamad Aiman Mohd; Ting, Hong Wei; Yuan, Yong Kai; Shah, Azim Wafiy Gulam; Loong, Tan Wan; Shaharulnizim, Nurshahirah; Reduan, Mohd Farhan Hanif; Hamid, Fathin Faahimaah Abdul; Noralidin, Nur Amalina; et al. (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: This short study describes the occurrence of pathogenic Leptospira spp. in two major wet markets in Kota Bharu, Kelantan, Malaysia. Materials and Methods: 30 rodents (20 rats and 10 shrews) were caught in 2 wet markets, and a postmortem was performed to extract both kidneys. Molecular diagnosis via polymerase chain reaction (PCR) was conducted to detect leptospiral DNA using universal and pathogenic Leptospira primers, respectively. Results: The results showed that 20/28 (72%) rat samples were detected positive for Leptospira spp, and all shrews were negative. Further sequencing analysis identified L. interrogans and L. borgpetersenii as the most frequently Leptospirosis species from kidney samples. Conclusions: The presented study here sheds light on the presence of pathogenic leptospires harboring the rat population in both wet markets in Kelantan, which presents a great public health risk to wet market workers and visitors. J. Adv. Vet. Anim. Res., 9(2): 275–281, June 2022 http://doi.org/10.5455/javar.2022.i593